Fish and Fisheries in the Sesan River Basin - Baran, Eric; Saray, Samadee; Teoh, Shwu Jiau; Tran, Thanh Cong (CGIAR Challenge Program on Water and Food, 2011)
The present component of the project focussing on i) the Sesan Basin and ii) fisheries will: ‐ establish a fisheries baseline for the Sesan catchment, focussing on fish biodiversity, fish production, fisheries zoning, resource use and the fisheries sector; ‐ Identify ecological flows suitable for fish in the Sesan catchment (how much flow should be left for downstream fish production); ‐ contribute to the identification of a set of ecological sustainability principles which will guide multiple uses of water resources and riverine systems; ‐ assess the impacts of dam development on the fisheries sector (how much capture fish will be lost due to dam construction, how this loss can be mitigated, and how much fish can be produced from reservoirs).